The Hidden Traps of Digital Advertising: A Case Study on Azarine and Cleora Beauty - Nofiyanti Nofiyanti (Yayasan Aya Sophia Indonesia, 2025)
Developments in digital technology have driven major changes in communication patterns, including in product marketing strategies that use social media. Communication that is not delivered appropriately can contain logical fallacies that mislead audiences and damage brand reputation. This study aims to identify the types of logical fallacy that appear in the promotional content of two cosmetic brands, namely Azarine and Cleora Beauty, through the Instagram and TikTok platforms. The research uses a literature study method with a descriptive qualitative approach. The results show that Azarine uses fallacies such as Hasty Generalization, Appeal to Authority, and False Dilemma in its advertisements, while Cleora Beauty shows Ad Hominem fallacy, False Consensus Effect, Confirmation Bias, Hasty Generalization, and Bandwagon Fallacy. While these strategies are effective in attracting public attention, using them without factual basis and empathy can trigger negative sentiments and create a reputation crisis. Therefore, companies need to implement ethical, empathetic, and data-driven communication to maintain integrity and public trust.